(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This research, conducted within the framework of the European Interreg "Open Badges for IT" project explored an alternative to traditional measurement-centered evaluation in adult education. While standard assessment often focuses on results and external comparison, which often leaves little room for valuing the lived transformations of the learner, this work investigates "first-person assessment" by relying on a descriptive, non-comparative self-evaluation without pre-established templates or external value judgments. The study examines the "Selfie-Badge" as an intermediary object used to render visible transformations and competencies that are often "invisible," such as active listening, cooperation, or assertiveness, which echoes approaches to competence evaluation oriented toward recognition. The research also draws on the notion of "capacitating environments" that support the emergence of capabilities and a power to act. Using a Design-Based Research (DBR) methodology combined with design thinking, the study followed iterative cycles to prototype and refine the implementation of recognition and first-person assessment through the Selfie-Badge. The experimentation took place at the University of Lille with 13 adults enrolled in a continuing education master’s program. Data triangulation—including participant observation, in-depth interviews, and analysis of the badges produced—made it possible to identify specific "schemes", such as self-observation in action, and the collective identification of competencies, in reference to the theory of schemes and operational invariants. The dynamic of positive interdependence further fostered collective appropriation of the process and mutual recognition among participants. These elements illustrate the "instrumental genesis" of the badge as it evolves from a simple artifact into an instrument of subjectivation and empowerment, echoing work on instruments, activity, and development of the power to act. The results highlight the emergence of a "capacitating space" that strengthens the learner’s "power to act," understood as the ability to say, "I can." At the same time, the study identified key points of vigilance, including the social legitimacy of self-assessment and the difficulties learners encounter in verbalizing their skills, which underline the need for structured methodological support to foster both individual and collective appropriation of first-person recognition. Selfie Badge, Power to Act, Positive Interdependence. Keywords: open badges, first-person assessment, continuing education, Selfie Badge